Fostering intercultural competence through videoconference exchange: using an external provider to match learners with trained native speakers and administer video calls - Alonso Varo Varo (University of Groningen Press, 2021)
This practical case presents the use of an External Provider (EP) as an alternative approach to the traditional telecollaboration setting where a partnership with a foreign higher education institution is established. Usually, these partnerships involve language exchanges between learning partners who mutually practice each other's native language. Instead, an eight-week cross-cultural Virtual Exchange (VE) in Spanish between US college students studying Spanish and trained Colombian university students was organized through an external language platform to foster the US students' Intercultural Competence (IC). It is concluded that the use of an EP brings an undeniable level of flexibility to the organization of the VE, and makes manageable the integration of this type of program in higher education language classes. Additionally, this article assesses the value of this approach by looking at the effect of VE on the US students' self- assessment of IC after the videoconference exchanges. Data from quantitative surveys and student blogs show a significant increase in the students' IC after the program.